The Heat Exchanger Thermal Degradation Process Determinants within the Steam Power Plants - T. Hajduk (Scientific Journal of Gdynia Maritime University, 2017)
he deposits presence on the heat transfer surfaces of the heat exchangers within the stationary and the ship steam power plants cause an inscrease in terminal temperature difference values and entails a decrease of the vacuum level, as well. That fact leads to reducing the total efficiency of the thermal unit. Symptoms of heat degradation are usually defined as the difference between the values of thermal-flow parameters for the current and the reference state. Moreover, thermal degradation of any heat transfer device always entails an increase in the cost of energy conversion, leading to increasing the emission output of greenhouse gases and finally increasing the environmental degradation process. The above-mentioned phenomena, the determinants of the thermal degradation as well as the results of the author’s own experimental research have been presented in the paper.